Neotropical tree production: insights into germination, growth and outplanting for Maytenus boaria - Marro, Nicolás Alejandro (2017)
Knowledge about tree production practices is essential to support forestrestoration projects, but is still lacking for many tree species. Maytenus boaria is a neotropical tree distributed across the temperate and subtropical South American mountains. In central Argentina, it is mainly restricted to the most preserved forest remnants. Attempts to plant this species have had little success due to difficulties in seedling production and low seedlingsurvival. We set up four trials aiming to identify the constraints of seedling production and outplanting. Under greenhouse conditions, we evaluated (i) pre?germination treatments and (ii) seedling response to inoculation with arbuscular mycorrhizal fungi (AMF). In the field, we planted M. boaria saplings as well as saplings of the most abundant tree in our study site and recorded (iii) survival and height for 10 years. Finally, (iv) we quantified natural recruitmentin an attempt to determine M. boaria regeneration niche. Germination varied from 13.1 to 29.2% among treatments. Depulped seeds stratified at 5 oC showed the highest germination (29.2%). Shoot phosphorus concentration in AMF-treated seedlings was significantly higher (45%) than in non-inoculated seedlings. Survival of M. boaria saplings was similar to that of the most abundant tree in our study site, but their lower height suggested limited growth.We recorded low abundance of M. boaria seedlings in the field; therefore, we were unable to identify the characteristics of its regeneration niche. Reforestation activities should include seed depulping and stratification at 5 oC to improve germination. The capacity of AMF to enhance nutrition should be evaluated under field conditions.